The Design and Development of Aquaponics Piping System for Urban Farming - Mohamad Ariffin, Muhammad Zahid; Abdul Mutalib Leman; Khairunnisa A. Rahman (Progress in Engineering Application and Technology, 2022)
Aquaponics is a recirculation system that combines aquaculture units and hydroponics units in one system to facilitate consumers living in urban areas to get a supply of fresh and nutritious vegetables and fish protein. The Aquaponics system that I developed is using the Nutrient-Film Technique (NFT) system. To fabricate this system, three designs were developed to compare and select designs that are capable of maximizing production and affordable development costs. The objective of this project is to design and fabricate an aquaponic system and test its level of effectiveness on water, energy, and nutrients. After finalizing the design, the preparation of equipment such as water tanks, biofilters, hydroponic units made of PVC pipes, and pumps is done to start the fabrication process. After completing the fabrication process, add Anabas Testudineus fish (climbing perch) and Lettuce and Pak Choi plants. After that, test the levels of ammonia, nitrite, residual chlorine and pH values ​​and collect data. The proper use of biofilters affects the effectiveness of water quality. Based on the collected results, the levels of ammonia and nitrite in this system are in optimum levels throughout the operation of this system. The pH and residual chlorine values ​​are also at appropriate rates for aquaponic systems. This shows, the biofilter used is suitable and effective. My suggestion is, consumers need to be smart in choosing the type of fish and vegetables they want to use in this system and need to know the appropriate ratio of total fish to how many units of vegetables.